2016
DOI: 10.1016/j.jtcme.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Tongue color changes within a menstrual cycle in eumenorrheic women

Abstract: Tongue color (舌色 shé sè) has been used to diagnose abnormal body conditions for thousands of years in traditional Chinese Medicine (中醫 zhōng yī). However, it is not clear whether tongue color alters with physiological changes within a normal menstrual cycle (月經周期 yuè jīng zhōu qī). This study investigated difference in tongue color between the follicular phase and luteal phase in eumenorrheic women. Tongue surface photographs were taken in the follicular phase and the luteal phase of thirty-two volunteers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…[31,32] The sample sizes were 12, 7 and 4 for follicular phase, luteal phase and hemorrhagic phase, respectively, in the first collection and 14, 6 and 3 respectively in the second collection.…”
Section: Methodsmentioning
confidence: 99%
“…[31,32] The sample sizes were 12, 7 and 4 for follicular phase, luteal phase and hemorrhagic phase, respectively, in the first collection and 14, 6 and 3 respectively in the second collection.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is thought that tongue features change in the presence of several diseases, including anemia, appendicitis, cancer, diabetes, immune hepatic injury, and gastrointestinal disease [12, 13, 26]. For example, a reddish-purple tongue and thin tongue coating usually indicate blood stasis syndrome or blood stagnation [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Hsieh et al found that the greatest differences in color values between the follicular phase and the luteal phase were observed in healthy subjects with normal cycles [ 14 ]. Zhang et al found that the color of the tongue varied from darker red to pink during the menstrual cycle [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations